1997
DOI: 10.1172/jci119854
|View full text |Cite
|
Sign up to set email alerts
|

Human beta-2 adrenoceptor gene polymorphisms are highly frequent in obesity and associate with altered adipocyte beta-2 adrenoceptor function.

Abstract: Catecholamines play a central role in the regulation of energy expenditure, in part by stimulating lipid mobilization through lipolysis in fat cells. The beta-2 adrenoceptor (BAR-2) is a major lipolytic receptor in human fat cells. To determine whether known polymorphisms in codons 16, 27, and 164 of this receptor play a role in obesity and subcutaneous adipocyte BAR-2 lipolytic function, we investigated a group of 140 women with a large variation in body fat mass. Only the polymorphisms in codons 16 and 27 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
365
4
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(395 citation statements)
references
References 28 publications
18
365
4
8
Order By: Relevance
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9]. Previous studies have suggested sex differences [16].…”
Section: Discussionsupporting
confidence: 92%
“…The Arg allele frequency of the ADRB2 Arg16Gly variant (38%) was similar to previously identified allele frequencies [2,4,5]. The present case-control study, quantitative trait analysis and meta-analysis did not provide evidence of an impact of the variant on obesity, which is consistent with previously performed case-control studies [2,[4][5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…6 The importance of the ADRB system in cardiovascular physiology has been explored on multiple levels and led to the discovery of multiple polymorphic variants in this system ( Figure 1). 14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] ADRB1 polymorphisms Twenty-three polymorphisms of ADRB1 have been described and 13 of these predict amino-acid changes in the ADRB1 protein. 14,40 As ADRB1 does not have a recognized role in the pathogenesis of asthma, the majority of genetic association studies have focused on cardiovascular phenotypes.…”
Section: Introductionmentioning
confidence: 99%